Macroeconomic Costs of Higher Bank Capital and Liquidity Requirements - Roger, Scott (IMF Working Papers; Working Paper, 2011)
This paper uses a DSGE model with banks and financial frictions in credit markets to assess the medium-term macroeconomic costs of increasing capital and liquidity requirements. The analysis indicates that the macroeconomic costs of such measures are sensitive to the length of the implementation period as well as to the adjustment strategy used by banks, and the scope for monetary policy to respond to the regulatory changes.